Pembinaan Pembelajaran Catur Pakeliran Bagi Siswa Lembaga Pendidikan Ketrampilan Kursus Pedalangan Sekar Rinonce Di Wonogiri - Kuwato Kuwato (Abdi Seni, 2016)
Community serving activities entitled â€œEducational Training of CaturPakeliran for the Students of SekarRinonce Pedalangan Training Course in Wonogiriâ€ was held to increase the skill of catur for the students of SekarRinoncePedalangan Training Course and also to improve the quality of catur learning, by using innovative model and strategy.The core competences of catur pakeliran which given to the students, cover : janturan, pocapan, and ginem in the first scene (jejer), Kedhatonan,Paseban Jawi,AdeganDuryapura, and the scene of perang gagal in the lakonWahyu Makutharama which arranged by Purwadi. This aducational training of catur pakeliran is considered succeed, because of the whole quality of the students in presenting garap catur is a lot better than before. This improvement of skill in performing catur cannot be separated from the learning method of active-independent education for the student which used several methods of speech, appreciation, and demonstration. This model of active-independent education explores studentsâ€™â€™creativity, soÂ that they can respond the material of training given by creative skills. This conclusion is based on evaluation towards the trainers which observe their students in the last session of performance of this educational training. Keywords : Catur Pakeliran, Seker rinonce, PedalanganÂ